INTEGRATING DIGITAL TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN FOREIGN LANGUAGE TEACHING - Karimova Umida Ochilovna; Ravshanova E'zoza Ildar qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  This  study  offers  a  thorough  academic  investigation  into  the transformative impact of digital technologies and artificial intelligence (AI) on foreign language teaching. The research explores how novel approaches, including adaptive learning  systems,  smart  tutoring,  and  immersive  virtual  settings,  are  transforming conventional  teaching  frameworks.  Through  examining  the  incorporation  of  AI-powered tools, the article illustrates their ability to offer tailored feedback, improve language  skills,  and  promote  learner  independence.  The  results  indicate  that  a curriculum  enhanced  by  technology  fosters  a  deeper  understanding  of  language frameworks  and  cultural  settings.  The  study  finds  that  the  combination  of  human teaching methods and technological advancements is crucial for attaining greater levels of communication skills in the contemporary age.